2020
DOI: 10.1080/22221751.2020.1720527
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pyrvinium pamoate as an anti-tuberculosis agent in vitro and in vivo by SOSA approach amongst known drugs

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (M.tb) bacteria, is a leading infectious cause of mortality worldwide. The emergence of drug-resistant M. tb has made control of TB more difficult. The selective optimization of side activities (SOSA) approach uses old drugs for new pharmacological targets. In the present study by using SOSA approach, we have successfully identified pyrvinium pamoate (PP) which is capable of inhibiting the growth of mycobacteria, including M. tb H37Rv, Mycobacterium smegm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Unsurprisingly, multiple antibiotics have displayed significant efficacy against cancer cells through inhibiting the mitochondria [ 104 , 105 , 106 , 107 ]. PP, interestingly, was first found to be an anti-mitochondrial agent, and only subsequently found to show significant activity against bacteria including Mycobacterium tuberculosis [ 29 , 30 , 31 ].…”
Section: Pp Mechanisms Of Action As An Anti-cancer Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, multiple antibiotics have displayed significant efficacy against cancer cells through inhibiting the mitochondria [ 104 , 105 , 106 , 107 ]. PP, interestingly, was first found to be an anti-mitochondrial agent, and only subsequently found to show significant activity against bacteria including Mycobacterium tuberculosis [ 29 , 30 , 31 ].…”
Section: Pp Mechanisms Of Action As An Anti-cancer Agentmentioning
confidence: 99%
“…Although the use of PP as an anthelminthic has dwindled over the years, since the early 2000s, interest in PP has surged due to its potential utilization to target other diseases-causing organisms at every level from viral [ 27 , 28 ] through bacterial [ 29 , 30 , 31 ], plasmodium [ 32 ], and fungi [ 33 , 34 , 35 ] to multicellular organisms [ 36 ] ( Figure 2 ). PP has also shown significant potential in multiple disease types for the ability to reduce toxicity, promote wound repair, and inhibit fibrotic tissue development [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tran et al demonstrated that the use of cationic cubosomes as a delivery vehicle reduced the minimum inhibitory concentration (MIC) of RIF against Staphylococcus aureus compared to free RIF . However, while the inhibitory effect of free RIF against TB has been well-studied, the use of cubosomes to deliver RIF or other ATDs has not yet been investigated to our knowledge. Herein, the inhibitory effect of MO-DOTAP-RIF cubosomes was initially investigated against the active replicating stage of MTB-H37Ra in the presence of increasing lipid concentrations (2.5–12.5 μg/mL) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanisms by which PVP, THP and 06 affect adult and larval filarial worms are unknown. In addition to its other anti-parasitic activities, studies have shown that PVP inhibits the proliferation of tumor cells across a range of in vitro and in vivo models of various types of cancers, including colon, breast, lung, prostate, pancreatic cancer, myeloma and lymphoma and has also shown potential as an anti-tuberculosis agent [13,[40][41][42][43]. Potential targets of PVP include the Wnt signaling pathway, the Hedgehog pathway, androgen receptors, mitochondrial respiration and glycolysis and further study is needed to determine if PVP and its analogs target similar pathways in filarial worms.…”
Section: Discussionmentioning
confidence: 99%